Ginsenoside Ro ameliorates cognitive impairment and neuroinflammation in APP/PS1 mice via the IBA1/GFAP-MAPK signaling pathway - Li, Tianyao; Chen, Jiaxin; Xie, Zhouyuan; Fang, Jiansong; Wu, Qiqing; Cao, Xinyue; Chen, Ziying; Wang, Yiyun; Fan, Qiqi; Wang, Qi; Liu, Jinman (Frontiers in Pharmacology, 2025)
IntroductionGinseng, known as the “king of herbs,” has long been used in traditional Chinese medicine due to its beneficial properties, including anti-aging, anti-inflammatory, and anti-apoptotic effects. Ginsenosides, the active compounds in ginseng, have shown promise in treating neurodegenerative diseases such as Alzheimer’s disease (AD). This study investigates the therapeutic potential of Ginsenoside Ro and its underlying mechanisms in AD treatment.MethodsIn this study, male APP/PS1 transgenic mice were divided into five groups and treated with Ginsenoside Ro or ginseng for one month. Cognitive function and anxiety were assessed through behavioral tests, including the open field test (OFT) and Morris water maze (MWM). To evaluate Aβ deposition, neuronal apoptosis, neuroinflammation, and the MAPK pathway, various techniques were employed: Thioflavin-T staining, Nissl staining, immunofluorescence, Western blot, and qRT-PCR analyses.ResultsGinsenoside Ro significantly improved cognitive function and reduced anxiety in APP/PS1 mice. It also decreased Aβ deposition and ameliorated neuronal apoptosis in the cerebral cortex. The treatment regulated the expression of pro-apoptotic proteins (Bax and Caspase3) and increased the anti-apoptotic protein Bcl-2. Additionally, Ginsenoside Ro reduced neuroinflammation by decreasing IBA1-positive microglia and GFAP-positive astrocytes and lowering pro-inflammatory cytokines while enhancing anti-inflammatory cytokine IL-10. Furthermore, the phosphorylation levels of p38 and JNK in the MAPK pathway were significantly reduced, suggesting a key mechanism for its therapeutic effects.DiscussionThese findings provide strong evidence supporting Ginsenoside Ro as a potential therapeutic agent for Alzheimer’s disease. Its effects appear to be mediated through the modulation of the IBA1/GFAP-MAPK pathway, which may offer new insights into AD treatment strategies.